2018
DOI: 10.1007/s00426-018-1083-7
|View full text |Cite
|
Sign up to set email alerts
|

More than simple facts: cross-linguistic differences in place-value processing in arithmetic fact retrieval

Abstract: Linguistic specificities such as the inversion property of number words (e.g., in German 43 is spoken dreiundvierzig, literally three and  forty) moderate Arabic number processing. So far, cross-linguistic studies have mostly focused on inversion-related effects on simple (e.g., number comparison) and calculation-based (e.g., multi-digit addition) magnitude processing of numerical information. Despite the assumption that multiplication facts are represented in verbal format, not much attention has been paid to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 40 publications
4
20
1
Order By: Relevance
“…Moreover, another explanation that could be invoked could be related to the difference in the way of expressing the numbers in French and in Dutch, in which the order is different, e.g., in Dutch, 45 is spoken vijfenveertig, literally five and forty. Indeed, Bahnmueller, Göbel, Pixner, Dresen, & Moeller [ 49 ] have reported that Arabic number processing could be moderated by linguistic specificities, such as the inversion property of number words. Despite the fact that some studies evaluating the influence of linguistic properties on processing place-value information have shown that number word inversion leads to additional processing costs in different numerical tasks [e.g., multi-digit addition: 27 ], some authors have suggested that inversion could actually be advantageous for the retrieval of the correct solution of some calculations [for further information, see 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another explanation that could be invoked could be related to the difference in the way of expressing the numbers in French and in Dutch, in which the order is different, e.g., in Dutch, 45 is spoken vijfenveertig, literally five and forty. Indeed, Bahnmueller, Göbel, Pixner, Dresen, & Moeller [ 49 ] have reported that Arabic number processing could be moderated by linguistic specificities, such as the inversion property of number words. Despite the fact that some studies evaluating the influence of linguistic properties on processing place-value information have shown that number word inversion leads to additional processing costs in different numerical tasks [e.g., multi-digit addition: 27 ], some authors have suggested that inversion could actually be advantageous for the retrieval of the correct solution of some calculations [for further information, see 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Bahnmueller, Göbel, Pixner, Dresen, & Moeller [ 49 ] have reported that Arabic number processing could be moderated by linguistic specificities, such as the inversion property of number words. Despite the fact that some studies evaluating the influence of linguistic properties on processing place-value information have shown that number word inversion leads to additional processing costs in different numerical tasks [e.g., multi-digit addition: 27 ], some authors have suggested that inversion could actually be advantageous for the retrieval of the correct solution of some calculations [for further information, see 49 ]. In the context of Dutch CLIL, the learning and the manipulation of two different number structures, like immersed children have to do as soon as in the third kindergarten, can have an early impact on the understanding of the place-value and, in turn, in the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on operant effects conducted in the context of multiplication fact retrieval (Bahnmueller et al, 2020 ; Domahs et al, 2006 , 2007 ) show the data for adults. However, little is known about whether the same problems can be found and replicated in children, who have not yet been able to build semantic networks for multiplication as strongly as adults.…”
Section: Introductionmentioning
confidence: 93%
“…Bahnmueller et al ( 2020 ) first used the link between language, specifically inversion-related effects, and place-value processing. They evaluated the decade-consistency effect and table-relatedness for multiplications in adults with different linguistic backgrounds.…”
Section: Influences Of Language On Numerical Processingmentioning
confidence: 99%
See 1 more Smart Citation